Site-directed mutagenesis and functional analysis of Eucalyptus sucrose synthase 1 (Egsusy 1) in Arabidopsis Thaliana - Myburg, Alexander Andrew (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.